2017
DOI: 10.1016/j.rmed.2017.10.014
|View full text |Cite
|
Sign up to set email alerts
|

Bronchopulmonary dysplasia: A review of pathogenesis and pathophysiology

Abstract: Bronchopulmonary dysplasia (BPD) is a chronic lung disease of primarily premature infants that results from an imbalance between lung injury and repair in the developing lung. BPD is the most common respiratory morbidity in preterm infants, which affects nearly 10, 000 neonates each year in the United States. Over the last two decades, the incidence of BPD has largely been unchanged; however, the pathophysiology has changed with the substantial improvement in the respiratory management of extremely low birth w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
207
0
11

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 290 publications
(261 citation statements)
references
References 131 publications
4
207
0
11
Order By: Relevance
“…The main pathologic finding of bronchopulmonary dysplasia (BPD) in the postsurfactant era is an alveolar arrest resulting in alveolar simplification (the development of fewer but larger alveoli with decreased septation) and decreased density of capillary beds [1][2][3][4][5][6] . Recent studies have revealed that impaired angiogenesis may lead to decreased numbers of alveoli; therefore, enhancement of normal angiogenesis could promote alveolarization in preterm infants 1,3,5,[7][8][9][10] .…”
mentioning
confidence: 99%
“…The main pathologic finding of bronchopulmonary dysplasia (BPD) in the postsurfactant era is an alveolar arrest resulting in alveolar simplification (the development of fewer but larger alveoli with decreased septation) and decreased density of capillary beds [1][2][3][4][5][6] . Recent studies have revealed that impaired angiogenesis may lead to decreased numbers of alveoli; therefore, enhancement of normal angiogenesis could promote alveolarization in preterm infants 1,3,5,[7][8][9][10] .…”
mentioning
confidence: 99%
“…Hyperoxia exposure in newborn rats closely mimics clinical conditions in preterm infants (Choi et al, ; Zhu et al, ). In our hyperoxia‐induced BPD mouse model, histological analysis of lung sections showed significant alveolar simplification and aberrant pulmonary vascularization (Figures b and c), which are the typical histopathological hallmarks of clinical BPD (Coalson, ; Kalikkot Thekkeveedu, Guaman, & Shivanna, ).…”
Section: Discussionmentioning
confidence: 69%
“…Prolonged oligohydramnios may be associated with neonatal pulmonary hypoplasia (16,20). It has been pointed out that various factors, including premature lungs, oxygen toxicity and in ammatory mediators, are also involved (21).…”
Section: Discussionmentioning
confidence: 99%